TINJAUAN LITERATUR TENTANG ANALISIS TEKS ULASAN SEBAGAI SARANA EVALUASI KARYA SASTRA DAN NONFIKSI - Jelita Geovani; Fathi Faliha Rusmini Sangkot; Anisa Ruth Sahanaya; Nova Sari Naibaho; Tiara Naprita; Nazwa Salsabila; Ayu Nadira Wulandari, M. I. Kom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Paragraph structure and development are essential aspects of academic writing because they contribute to the creation of scholarly works that are systematic, coherent, and easy to understand. The ability to construct effective paragraphs enables writers to communicate ideas clearly, logically, and purposefully, thereby achieving the objectives of academic communication. This article aims to review various studies and references on paragraph structure and development in academic writing and to analyze their contribution to improving the quality of scholarly works. The method employed is a literature review by examining relevant academic sources, including books, journals, research articles, and other scholarly references. The collected data were analyzed descriptively to identify key concepts related to paragraph structure and development techniques. The findings indicate that paragraph structure, consisting of a topic sentence, supporting sentences, and a concluding sentence, plays a crucial role in establishing unity, coherence, and logical connections among ideas within a text. Furthermore, paragraph development through various patterns, such as exemplification, cause-and-effect, comparison, definition, classification, and chronological order, helps clarify ideas, strengthen arguments, and improve the readability and effectiveness of academic writing. The proper application of paragraph structure also enables readers to comprehend information more systematically and supports effective message delivery. Therefore, a comprehensive understanding of paragraph structure and development can serve as an important factor in enhancing the quality of academic writing in terms of clarity, organization, and effectiveness of scholarly communication.